Exploring the Anti-Inflammatory Potential of Cyperus pangorei Rhizome Extracts An In Vitro and In Vivo Study (International Journal of Ayurveda and Pharma Research, 2024)
Background and aim: Inflammation is a pivotal process implicated in various physiological and pathological conditions, necessitating the exploration of alternative anti-inflammatory agents with minimal side effects. This study aimed to investigate the anti-inflammatory potential of the standardized ethyl acetate (EtAc) fraction derived from Cyperus pangorei rhizomes. Methods: The rhizomes of C. pangorei were collected, processed, and subjected to extraction and fractionation to obtain the EtAc fraction. RP-HPLC analysis was employed to standardized the EtAc fraction against standard quercetin, luteolin, and apigenin. In vitro studies utilized peritoneal macrophages isolated from male Swiss albino rats to assess NO production and cytokine levels (IL-1β, IL-6, TNF-α) upon treatment with the EtAc fraction. In vivo evaluation was conducted using a carrageenan-induced rat paw edema model. Results: RP-HPLC analysis revealed the presence of quercetin, luteolin, and apigenin in the EtAc fraction. In vitro studies demonstrated dose-dependent inhibition of LPS-induced NO production and suppression of inflammatory cytokines (IL-1β, IL-6, TNF-α) by the EtAc fraction. Furthermore, in the carrageenan-induced rat paw edema model, the EtAc fraction exhibited dose-dependent inhibition of paw edema. Conclusion: The findings of this study highlight the significant anti-inflammatory potential of C. pangorei rhizome extracts, particularly the EtAc fraction. The identified compounds, quercetin, luteolin, and apigenin, contribute to its anti-inflammatory activity by modulating key inflammatory mediators. These results support the potential therapeutic use of C. pangorei in managing inflammation-related disorders. Further research is warranted to elucidate the underlying mechanisms and evaluate the long-term efficacy and safety of C. pangorei extracts as anti-inflammatory agents.